Administrative and legal forms and methods of preventing the national police units of public security from illegal migration - Drakokhrust, Tetiana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The article deals with the peculiarities of administrative legal forms and methods of preventing the national police units of public security from illegal migration. Auto specifies the entire list of legal acts that regulate the measures of the law-enforcement bodies of Ukraine to prevent illegal migration. The author emphasizes that the administrative activities of the police in combating illegal migration have specific characteristics. The article also notes that significant efforts to prevent illegal migration are being carried out by public security units, most notably the detachment of detainees. Supervision is considered as a separate type (form) of control, the application of which in the detection of violations may be accompanied by measures of influence of the state-power character. The main form of prevention of illegal migration by the units of the public security police is the conduct of special operations: "Migrant", "Foreigner", "Border", "Border", "Entrepreneur", "Student", etc. The administrative service of the Ministry of Internal Affairs of Ukraine monitors on a monthly basis the detained illegal migrants who are in detention centers and temporary detention centers. The author notes that by joint actions the territorial bodies and units of the LCA and the NGU have identified and made a decision on the forced return of migrants, foreigners have been placed in temporary detention centers for foreigners and stateless persons, banned entry into Ukraine. The author has come to the conclusion that the most active methods of preventive work are the method of warning using the media, diplomatic and consular institutions of other countries and the exchange of information with law enforcement agencies of Ukraine and other countries. There is an urgent need for effective interaction between public authorities to prevent illegal migration and to create an image of the state capable of controlling its own territory, protecting state borders and ensuring a high level of national security in the migration sphere.